When crime waves - Sacco, Vincent (SAGE Publications, 2005)
When Crime Waves offers an in-depth exploration of a large number of social issues involved in the study of crime waves. Issues such as how and why crime rates change over time, why some types of crime and not others come in waves, and the role played by the mass media, politicians, and interest group leaders in the promotion of crime waves are discussed to help students develop analytical skills and apply them to real-world situations. offers an in-depth exploration of a large number of social issues involved in the study of crime waves. Issues such as how and why crime rates change over t.